Identificação de Áreas de Especial Interesse Peatonal (AEIP) utilizando análise multicritério e ferramentas de geoprocessamento - Gobbo, Caio Augusto Rabello (Universidade Federal de São Carlos, 2019)
The quality of pedestrian-oriented urban spaces is fundamental for economic development, public health, social welfare and environmental sustainability of a municipality. Many researchers base their studies on structural analysis of sidewalks and audits of spaces, considering aspects related to the safety, security, and attractiveness of the environment. However, there is a lack of studies that correlate characteristics of urban land use and occupation, as well as sociodemographic characteristics for the identification of urban spaces that are a priority to the focus on pedestrian. With the prioritization, the public management can identify punctually where to act to carry out studies, bring significant improvements to the walkability and choose, among the areas of the municipality, those that need more attention. Thus, the present study aims to develop a method that, based on the correlation of land use and socio-demographic variables, indicates such priority areas, named as Areas of Special Pedestrian Interest (AIEP), that is, priority areas for future analyzes and improvements related to the quality of pedestrianized urban space. The following steps are developed in the study: (i) selection of relevant variables, (ii) ranking variables according to hierarchical process analysis (AHP) in expert research, (iii) representation of results in GIS platform, (iv) identification of the AEIPs and (v) analyzing the walkability in selected zones. For the development of the method, the city of São Carlos (SP) is used as a study area because of the availability and ease of data collection, but it is expected that the method will be replicable in other scenarios. The results indicate about 1522ha of the urban region (19%) as (AEIP), extrapolating the consolidated urban center. Several "center of neighborhoods" regions are identified, presenting mixed occupation profile (residential, commercial and service uses). These areas are synthesized in 79 priority census tracts, encompassing about 60,000 inhabitants (27.1% of the population) and 50 km of road extension - highlighting roads of great structural, commercial and circulation importance to the municipality. The developed method was able to identify priority areas (AEIPs), correlating land use and socio-demographic characteristics and presenting guidelines for regions that need more attention in the pedestrian area and contributing to the management of municipal walking mobility.
Keywords: Mobilidade urbana; Caminhabilidade; Transporte ativo; AHP; SIG; Urban mobility; Active transportation; Walkability; ENGENHARIAS::ENGENHARIA CIVIL::INFRA-ESTRUTURA DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES; ENGENHARIAS